2016
DOI: 10.15376/biores.11.3.6151-6161
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Maize Stalk Rind

Abstract: Experiments were carried out to measure the tensile properties of maize stalk rind. Two varieties of maize stalk (SD 12 and SD 9) and two moisture contents (fresh and air-dried) were tested. From each maize stalk sample, nine specimens (test coupons) of stalk rind were prepared to represent nine internodes from the bottom to the top of the maize stalk. The rind specimens were subjected to uniaxial tensile loading at a slow rate of 3 mm/min. From the recorded load-elongation curves, tensile stresses, modulus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Tensile testing is another common technique for obtaining the modulus of elasticity. This approach has been used to measure the modulus of elasticity of wood [ 7 ], excised rind sections of maize stems [ 15 , 16 ], excised longitudinal sections of switchgrass stems [ 17 ], rice stems, and Arabidopsis stems [ 18 ]. However, sample preparation is more laborious as compared to bending and specimens must be gripped securely without inducing tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile testing is another common technique for obtaining the modulus of elasticity. This approach has been used to measure the modulus of elasticity of wood [ 7 ], excised rind sections of maize stems [ 15 , 16 ], excised longitudinal sections of switchgrass stems [ 17 ], rice stems, and Arabidopsis stems [ 18 ]. However, sample preparation is more laborious as compared to bending and specimens must be gripped securely without inducing tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest estimate in the literature was 0.26 GPa obtained using internodal specimen with a length-to-diameter ratio of 1:1 under compressive loads [ 11 ]. The maximum estimate was 20 GPa obtained using dogbone shaped specimens in tension [ 14 ]. In this study, straight-sided specimens were used for tensile testing as recommended when testing fiber reinforced materials having comparable dimensions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex structure of maize stalks as well as the above-mentioned testing challenges, biomechanical data on the material properties of maize stalk tissues are currently limited to a handful of studies. These have included the determination of the compressive modulus of elasticity using dry internodal specimens with a length-to-diameter ration of 1:1 [ 11 ], bending modulus of elasticity of moist maize internodal specimens sampled at the pre-tasselling and dough growth stages [ 12 , 13 ], the tensile modulus of elasticity of moist and dry rind tissue of maize stalks [ 14 ], and a reduced modulus of elasticity (indentation modulus) of dry rind fibers using nanoindentation [ 15 , 16 ]. Most of these studies utilized only a single test method, and the reported values for rind modulus varied between 0.26 and 20 Gpa.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous makeup and properties of corn stover and softwood logging residues have proven to be difficult barriers to overcome using traditional preprocessing techniques, including milling, air classifying, and screening. The shear and impact forces required to break the various anatomical fractions of corn stover (rind, pith, leaf, husk, and cob) differ by tissue type (Anazodo, 1980;Zhang et al, 2016Zhang et al, , 2017Workiye and Woldsenbet, 2019). Applying sufficiently high impact and shear force to fracture tough components such as cob, husk and rind will pulverize the more fragile components such as pith and leaf, which leads to wide particle-size distribution with a high proportion of fines.…”
Section: Biomass Preprocessing and Fractionationmentioning
confidence: 99%